Bonhoeffer, Congar, and the Public Role of Faith - Berry, John Anthony ca. 21. Jh. (International journal of public theology, 2025)
This article explores the complementary theologies of Yves Congar and Dietrich Bonhoeffer, emphasizing their shared conviction that faith must actively engage with societal and political realities. Bonhoeffer’s prophetic resistance challenges the church to confront systemic injustices with moral clarity, while Congar advocates for a dialogical, renewal-driven approach to public theology. Their theological insights provide a framework for understanding the transformative role of faith in the public sphere, especially in response to the political and societal challenges of their respective contexts. The article proceeds by first contextualizing the distinct historical and ecclesial settings of both theologians, followed by a comparison of their theological approaches. It then examines their convergences, such as their shared emphasis on community, responsibility, and the public role of faith, before addressing their divergences in ecclesiology and engagement with the world. The research offers novel insights into how these two theologians can inform contemporary public theology by integrating prophetic critique and dialogical engagement.